2014
DOI: 10.1007/s11858-014-0655-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition in dot comparison tasks

Abstract: Dot comparison tasks are commonly used to index an individual's Approximate Number System (ANS) acuity, but the cognitive processes involved in completing these tasks are poorly understood. Here we investigated how factors including numerosity ratio, set size and visual cues influence task performance. Forty--four children aged 7--9 years completed a dot comparison task with a range of to--be--compared numerosities. We found that as the size of the numerosities increased, with ratios held constant, accuracy de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
91
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(101 citation statements)
references
References 57 publications
9
91
1
Order By: Relevance
“…These studies add further evidence that participants’ performance on dot comparison tasks is influenced by characteristics of the task (Clayton et al., 2015; Clayton & Gilmore, 2015; DeWind & Brannon, 2016; Gebuis & Reynvoet, 2012; Inglis & Gilmore, 2013, 2014; Price et al., 2012; Smets et al., 2015). In particular, we have shown that the visual characteristics of dot arrays affect the accuracy of numerosity judgements, and therefore performance on dot comparison tasks is not a pure measure of the acuity of ANS representations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies add further evidence that participants’ performance on dot comparison tasks is influenced by characteristics of the task (Clayton et al., 2015; Clayton & Gilmore, 2015; DeWind & Brannon, 2016; Gebuis & Reynvoet, 2012; Inglis & Gilmore, 2013, 2014; Price et al., 2012; Smets et al., 2015). In particular, we have shown that the visual characteristics of dot arrays affect the accuracy of numerosity judgements, and therefore performance on dot comparison tasks is not a pure measure of the acuity of ANS representations.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that performance on dot comparison tasks, and hence estimates of ANS acuity, are influenced by the numerosity of the dot arrays (Clayton & Gilmore, 2015), the method of presentation (i.e. sequential vs. simultaneous; Price, Palmer, Battista, & Ansari, 2012), the display time (Inglis & Gilmore, 2013) and the measure of performance used (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been suggested that accuracy on incongruent trials, rather than congruent trials, is related to mathematical achievement and that the relationship between the ANS and mathematical achievement can be attributed to the confound of inhibitory control (Gilmore et al . ; Clayton & Gilmore ). Specifically, poor inhibitory control may result in difficulty inhibiting an incorrect response to incongruent trials, resulting in participants selecting the set with larger individual dots, rather than a larger quantity of dots.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, poor performance on incongruent trials of the dot comparison task has been associated with poor inhibitory control, as these trials require the participant to inhibit a response based purely on stimulus characteristics (Gilmore et al . ; Clayton & Gilmore ). Thus, it has been suggested that the relationship between the ANS and mathematical achievement is attributable to the confound of inhibitory control (Gilmore et al .…”
Section: Introductionmentioning
confidence: 99%